Strokovne analize v prostorskem planiranju - Černe, Andrej (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2005)
Spatial analysis contributes to accomplishment of the three basic aims of spatial planning: it is basic element for setting spatial policies, concepts and strategies, gives basic information to inhabitants, land owners, investors, planners and helps in performing spatial policies, strategies, plans, programmes and projects. Analysis in planning are generally devoted to: understand current circumstances and emerging conditions within planning decisions; determine priorities of open questions and their solutions; formulate general principles for further development.
Keywords: regionalno planiranje; prostorsko planiranje; spatial planning; regionalni razvoj; analize; Slovenia; Slovenija